Postpartum bacteraemia outbreak due to Bacillus cereus in the delivery room - P. Xaplanteri; A. Chondroleou; F. Kolonitsiou; A. Skintzi; E.D. Anastassiou; M. Marangos; I. Spiliopoulou (New Microbes and New Infections, 2019)
We report an outbreak Bacillus cereus causing postpartum bacteraemia in the maternity ward and delivery room. Spores transferred by the hands and gloves of the staff in the maternity ward contaminated equipment in these two areas. Keywords: Bacillus cereus, bacteremia, maternity ward, sterilization